SSR-HRM molecular characterization of the Colombian cultivated germplasm of Capsicum chinense Jacq. (Solanaceae) (2022)
This study was the first evaluation of the genetic diversity of cultivated populations of habanero pepper (Capsicum chinense) in Colombia using SSR-HRM. Three habanero pepper lines were characterized with eight microsatellite markers using the High-Resolution Melt (HRM) technique. Twenty-seven individuals from the HL-original line and 30 individuals each from derived lines HL-70 and HL67 were genotyped. Three microsatellites were monomorphic, and five were polymorphic; however, a high allelic diversity was detected in the homozygous state in the 87 individuals. The Ng8 marker differentiated the HL-original and HL-67 lines from the HL-70 line with HRM profiles. The analysis of molecular variance (AMOVA) revelated that 52% of the genetic variation existed within lines. The HL-67 line was more similar to the HL-original line than to the HL-70 line. HL-70 recorded the highest genetic diversity for the derived lines and, therefore, could be used in a new breeding program. In contrast, the HL-67 line, because of its high genetic homogeneity, could potentially be used to evaluate different environmental conditions to find optimal conditions that increase productivity and pungency. Finally, comparing the HRM profiles with the monomorphic markers (Ng 33, Ng 18 and Ng 10) differentiated the C. chinense and C. frutescens species, which was difficult because of high morphologic similarity between these two species and is usually evaluated at the flowering stage, while HRM profiles can be done at any plant stage.